Viewing the Future of Space Property Through the Lens of Colonialism - Ishaaon Sivansh (Washington University Global Studies Law Review, 2025)
In this note, I will first introduce the Space Race, its lasting impact, and the implications it places on our understanding of property law. I will then discuss common law colonial legal doctrines and their potential impact on space property law. I will also analyze the development of international treaties and agreements in the field of space law and evaluate the effectiveness of treaties compared to common law colonial doctrines. From there, I will discuss how current and future changes in technology and space exploration, including the role of private individuals and companies, will impact the current space law framework and discuss which aspects of international law and colonial law are suited or unsuited to meeting those challenges. Finally, I will gauge the important factors in developing a space property framework and introduce an alternative form of property governance that shares the values of past international agreements while simultaneously safeguarding the common interest in space in the future.
Keywords: space race; space property; colonialism; space law; international treaties; technology; space exploration